ENGLISH OAK FOREST PLANTATIONS CREATING EXPERIENCE WITH THE USE OF CONTAINERIZED SEEDLINGS IN FOREST ENTERPRISE “KHARKIV FOREST RESEARCH STATION” - Tarnopilskiy, P. B.; Danilenko, O. M.; Gupal, V. V.; Mostepanuk, A. A.; Gladun, G. B. (Forestry and Forest Melioration, 2018)
Introduction The introduction of new technologies of artificial reforestation and afforestation, which would ensure the efficient creation and growth of high-quality forest cultures of various purposes, involves the use of containerized planting material that guarantees high survival rate and energy of growth in the first years after planting. Container-grown planting material is widely used in developed countries for reforestation. Today the share of crops created using such planting material is 80–100 %. The purpose of research is to explore the effect of fertilizers, superabsorbents, humic and microbiological agents on the intensification of oak seedlings cultivation in individual containers and to study features of growth and development of forest crops created by containerized planting material. Materials and Methods The research was carried out in the breeding complex of Pivdenne Forestry of Kharkiv Forest Research Station (Kharkiv FRS) using container-growing planting material. The areas of the study included: determining the optimal size of the container and the substrate composition; evaluating the results of the use of fertilizers, humic and microbial agents to intensify the cultivation of planting material in containers. Results Plantations created by planting material with use of the cultivation methods of intensification grow better in comparison to control. Over the time, the difference in height between control and plantation variants, where planting material was grown with intensive methods, is increasing. It is within 5.2–27.3 % in 3-year-old plantations created by planting material grown in the open landfill, and from 6.6 to 36.4% in 8-year-old plantations. In 3-year and 8-year-old plantations created using greenhouse planting material, the difference is 2.9–15.0 % and 10.9–17.1 %, respectively. Variants with mycorrhizal inoculation of container substrate using 2 mg per container and application of microbiological preparation “Baikal” had shown the best growth. Conclusions The use of mycorrhizal and microbiological drugs have prolonged action because the mycorrhizal area grows with roots growing, and optimal ratio of soil microflora remains, which provides better growth of forest crops. Closing of forest plantations created by containerized planting material using the planting scheme of 5.0 ? 0.5–0.7 m and plantation density of 3–4 thousand units per ha happens on 4–5 year. Cultures created by the container-growing planting material meet the requirements of “Instructions for the design, technical acceptance, registration and quality evaluation of silvicultural objects” in height and density to consider them as wooded lands: at 5 years by the height in the third quality grade and by the density in the first grade, and at 6 years in the first or second quality grade by height.